In vitro percutaneous penetration test overview - Shahinfar, Sheeva; Maibach, Howard (Frontiers in Pharmacology, 2023)
Skin is a detailed, organized, and intricate niche in the human body. Topical and transdermal drugs are unique, in that their absorption is quite different from other routes of administration (oral, intramuscular, intravenous, etc…). A robust amount of research is required to approve the use of a drug - in vivo, in vitro, and ex vivo studies collectively help manufacturers and government agencies with approval of various compounds. Use of human and animal studies poses ethical and financial concerns, making samples difficult to use. In vitro and ex vivo methods have improved over the past several decades - results show relevance when compared to in vivo methods. The history of testing is discussed, followed by a detailed account of known complexities of skin and the current state of percutaneous penetration.